Helicobacter pylori Antigen But Not the Organism Is Occasionally Present Within Germinal Centers: Implications for Patient Management and Biology. (November 2020) - Nelson, Nya D.; Tondon, Rashmi; Fortuna, Danielle; Westerhoff, Maria; Swanson, Paul E.; Furth, Emma
Abstract : Helicobacter pylori infection is present in two thirds of the world's population and induces a myriad of human diseases, ranging from gastritis to gastric adenocarcinoma and mucosa-associated lymphoid tissue lymphoma. Detection is critical for treatment and may require immunohistochemical (IHC) staining when organisms are not visible on hematoxylin and eosin. We have encountered cases in which IHC for Helicobacter pylori failed to demonstrate curvilinear or coccoid organisms, but did show a reticular pattern of immunoreactivity involving the underlying germinal centers. We performed a systematic retrospective evaluation of the frequency of H. pylori germinal center immunoreactivity over a 54-month period through evaluation of 367 gastric specimens. H. pylori germinal center immunoreactivity was observed in 5% of cases with germinal centers. Nine of 11 (81%) patients with H. pylori germinal center immunoreactivity had concurrent or recent H. pylori infection, in comparison to 36% of patients with germinal centers present but no immunoreactivity (n=9 of 25 patients, P =0.03). None of the patients with germinal center immunoreactivity developed mucosa-associated lymphoid tissue lymphoma. In situ hybridization for H. pylori performed on 3 cases with positive germinal center IHC was negative for H. pylori nucleic acids within those germinal centers, demonstrating that only the antigen is present. This work demonstrates that H. pylori antigen, but not viable organisms, is present in germinal centers in 5% of gastric specimens, and is associated with recent or concurrent H. pylori infection. We advocate for reporting of all H. pylori germinal center immunoreactivity with a recommendation for ancillary H. pylori testing.